SYNTHESIS, CHARACTERIZATION, AND EVALUATION OF ANTIBACTERIAL AND ANTIDEPRESSANT ACTIVITIES OF NOVEL TETRASUBSTITUTED IMIDAZOLE DERIVATIVES - AKSHAY MURALI; ANUSHA SHAJI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of this study is to synthesize 10 novel tetrasubstituted imidazole derivatives and characterizations of them and to evaluate their antibacterial and antidepressant activities. Methods: Ten novel tetrasubstituted imidazole derivatives were synthesized on the basis of Radziszewski imidazole synthesis. They were purified by double crystallization, characterized by melting point, thin-layer chromatography, infrared, and nuclear magnetic resonance spectroscopy, and subjected to elemental analysis. They were evaluated for their antibacterial activity by agar disc diffusion method and antidepressant activity by forced swim method and tail suspension method. Results: The compounds were synthesized and characterized them, and the structure was confirmed. The compounds were designated as M1 to M10 depending on their substitution. The antibacterial activity was evaluated using disc diffusion test in Bacillus subtilis, Staphylococcus aureus, Pseudomonas aeruginosa, and Escherichia coli using ciprofloxacin 20 μg as standard. All the 10 test drugs show significant antibacterial activity in Gram-positive organism. The antidepressant activity of novel tetrasubstituted derivatives and standard clomipramine using forced swim test and tail suspension method is evaluated in rats. Synthesized novel tetrasubstituted derivatives show a promising antidepressant activity. Conclusion: The synthesized compounds find promising antibacterial and antidepressant activities.